Contemporary theories of learning learning theorists -- in their own words - Illeris, Knud. (London Routledge, 2009)
A collection of some of the most influential learning theorists. It collects chapters that explain both the complex frameworks in which learning takes place and the specific facets of learning, such as the acquisition of learning content, personal development, and the cultural and social nature of learning processes.
A comprehensive understanding of human learning / Knud Illeris -- Learning to be a person in society : learning to be me / Peter Jarvis -- What "form" transforms? : a constructive-developmental approach to transformative learning / Robert Kegan -- Expansive learning : toward an activity-theoretical reconceptualization / Yrjö Engeström -- Pragmatism : a learning theory for the future / Bente Elkjaer -- An overview on transformative learning / Jack Mezirow -- Multiple approaches to understanding / Howard Gardner -- Biographical learning within the new lifelong learning discourse / Peter Alheit -- Life cycles and learning cycles / John Heron -- Adult education as a technology of the self / Mark Tennant -- Culture, mind, and education / Jerome Bruner -- Experience in adult learning / Robin Usher -- "Normal learning problems" in youth in the context of underlying cultural convictions / Thomas Ziehe -- The practice of learning / Jean Lave -- A social theory of learning / Etienne Wenger -- Transitional learning and reflexive facilitation : the case of learning for work / Danny Wildemeersch & Veerle Stroobants.
Keywords: Learning -- Philosophy; Adult learning